A Review on Stabilization of Ladle Furnace Slag-Powdering Issue - Dash A.; Chanda P.; Tripathy P.K.; Kumar N. (My University, 2025)
Ladle furnace (LF) slag plays an important role in modern steel making in terms of quality and productivity. The major challenge of using LF slag is its dusting problem. The polymorphic transformation of β-dicalcium silicate (monoclinic) to γ-dicalcium silicate (Orthorhombic) at about 450 °C is the leading cause of its disintegration. Hydration of slag, thermal shrinkage, and slower cooling are other reasons which are mainly responsible for slag powdering. The presence of dust particles due to disintegration not only creates a problem for its valorization but at the same time causes environmental issues. It becomes necessary for the steel makers to find out possible solutions to prevent such disintegration of slag. This review paper represents a detailed analysis of possible industrial solutions available for preventing of disintegration of LF slag and also will assist the steel operators for its effective utilization in major applications. Graphical Abstract: [Figure not available: see fulltext.] © 2022, The Minerals, Metals & Materials Society.